P023 Disseminated Histoplasmosis in a Patient with Crohn's Disease Under Tumor Necrosis Factor Blocker Therapy: An Unusual Case. (December 2019) - Ferreira, Sandro; Nóbrega, Fernando Jorge; Araujo, Roberta; Santana, Rodrigo; Ramalho, Leandra; Martinelli, Ana; Troncon, Luiz Ernesto
Abstract : INTRODUCTION: Infliximab, an antibody against tumor necrosis factor (TNF) alpha with well-established efficacy and proven safety, is currently widely used in Crohn's disease treatment. Complications of this kind of treatment are due to immunosuppression and include an increased risk of serious infections and malignant neoplasms. Disseminated histoplasmosis is a granulomatous disease caused by the fungus Histoplasma capsulatum, which have immunodepression as a major risk factor. CASE: We present the case of a 39-year-old white man with refractory fistulizing ileocolonic Crohn's disease using infliximab associated with azathioprine and having also steroids courses. After two years using this immunosuppressive therapy, the patient presented with high fever (39.5°) for five days, with profuse sweating, and moderate pain in the left hypochondrium. The patient was hospitalized for investigation and tuberculosis, malignancy, autoimmune diseases and bacterial and viral infections were rapidly discarded. Clinical, laboratory and image signs of liver involvement prompted a guided percutaneous biopsy, which revealed granulomatous hepatitis, with the presence of fungal structures suggestive of Histoplasma capsulatum. Upon treatment with liposomal amphotericin followed by itraconazole, the patient showed an impressively positive clinical response. DISCUSSION: TNF-α is a proinflammatory cytokine produced by macrophages. This agent has a key function in the formation of granulomas, playing an important role in the host defense system against infectious diseases, including histoplasmosis. Inhibition of this cytokine by anti-TNF-α in the context of the treatment of IBD may potentially reduce the efficacy of host immune function in defense against infectious organisms, thus leading to an increased risk of infections. In the present case the underlying immunosuppressive therapy of our patient (azathioprine and infliximab, in addition to courses of corticosteroids) due to the character of Crohn's disease, in an individual with a history of contacts with birds and travel to areas endemic for histoplasmosis (mold sporulation can be accelerated by bat and bird feces) might have been a risk factor for reactivation of latent disease focus and evolution to disseminated form. The diagnosis of disseminated histoplasmosis often presents a great challenge, considering that it can affect any organ, and this circumstance can contribute to a "chameleon-like" clinical image and diagnostic errors. This unusual case of disseminated histoplasmosis in a patient with Crohn's disease using infliximab in combination with azathioprine and steroids emphasizes the need for surveillance of this uncommon but potentially lethal complication before starting TNF blockers therapy. CONCLUSION: TNF blockers, particularly when associated with other immunosuppressors, are a serious risk factor for opportunistic infections, including disseminated histoplasmosis. Thus, it is essential that disseminated histoplasmosis be remembered as a possible diagnosis in patients using immunosuppressive therapies.